Understanding solar PV through the MinUS-C module grounded in the ADDIE instructional model - Muhamad Kamarul Azman Sulaiman,; Lilia Halim,; Nurazidawati Mohamad Arsad,; Ruhizan Mohamad Yasin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The rapid advancement of renewable energy technology, particularly solar photovoltaic (PV) systems, necessitates improved knowledge and readiness for adoption among the younger generation. However, secondary school students often exhibit significant knowledge gaps regarding this technology, potentially hindering its future acceptance and usage. This study addresses this gap by developing the MinUS-C (Minecraft Urban Solar Community) learning module, grounded in the ADDIE instructional model, to systematically enhance students’ understanding and readiness for solar PV technology. The module's design involved five phases of the ADDIE model: analysis, design, development, implementation, and evaluation. Findings from pre, post and delayed post-assessments reveal a marked improvement and retain in students’ knowledge of solar PV concepts, such as electricity generation and PV system components, as well as their readiness to embrace this technology. The module effectively bridges the knowledge gap and fosters positive attitudes towards renewable energy adoption. This study contributes to educational literature by providing a structured, evidence-based module for promoting green technology literacy among secondary school students. The findings underscore the potential of integrating digital tools like the MinUS-C Module into science curricula to advance sustainable development goals, equipping students with critical skills and awareness for future energy transitions.